1989
DOI: 10.3109/01485018908986847
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial Infection and Male Infertility: An Epidemiological Study

Abstract: Chlamydia-positive genitourinary infections are common causes of male and female infertility. Semen abnormalities are often associated with Chlamydia infections. A large population of male patients, admitted to our clinic for genitourinary infection, were examined for genitourinary pathogens, including Chlamydia, and for semen abnormalities. There were higher abnormalities semen in Chlamydiainfected patients than either non-Chlamydia-infected or healthy controls. Chlamydia therapy by antimicrobial agents impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…This is in accordance with Hartmann's report, which isolated C. truchomatis in testes of a male with pyospermia [7]. Semen abnormalities are associated with chlamydia1 infections [4] and C. truchomatis is attached to spermatozoa recovered from the peritoneal cavity of patients with salpingitis [5]. However, no significant difference was observed between Chlumydiuinfected and noninfected patients when semen parameters (cell count, motility, bovine mucus penetration, and hypoosmotic swelling test) were compared [9].…”
Section: Discussionsupporting
confidence: 74%
“…This is in accordance with Hartmann's report, which isolated C. truchomatis in testes of a male with pyospermia [7]. Semen abnormalities are associated with chlamydia1 infections [4] and C. truchomatis is attached to spermatozoa recovered from the peritoneal cavity of patients with salpingitis [5]. However, no significant difference was observed between Chlumydiuinfected and noninfected patients when semen parameters (cell count, motility, bovine mucus penetration, and hypoosmotic swelling test) were compared [9].…”
Section: Discussionsupporting
confidence: 74%
“…trachomatis can attach to spermatozoa (Hanssen & Mardh, 1984) and can be present in cytoplasmic droplets of spermatozoa (Villegas et al, 1991). Previous studies have found a correlation between genital chlamydial infection and sperm quality (Custo et al, 1989), although other studies have reported contradictory findings (Eggert-Kruse et al, 1996;Gdoura et al, 2001). It is important to resolve this issue, since chlamydiae present in semen could be transmitted by adhering to spermatozoa, which may serve as vectors, spreading the pathogen to the uterus and Fallopian tubes.…”
Section: Introductionmentioning
confidence: 70%
“…In fact, a large number of studies have suggested that positive markers for Chlamydia infection are not associated with altered sperm parameters [18], [19], [46], [54][55]. Others, however, have found that Chlamydia infection correlates with reduced sperm motility [34]–[56], increased proportion of sperm abnormalities [57], significant reductions in semen density, sperm morphology, and viability [58] and increased likelihood of leukocytospermia [34]. In addition, Veznik et al (2004) reported decreases in seminal plasma, sperm mobility, velocity, and normal morphology in C. trachomatis –infected infertile patients compared with those without infection [59].…”
Section: Discussionmentioning
confidence: 99%